2016
DOI: 10.1038/srep27531
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibition of apicoplast tryptophanyl-tRNA synthetase causes delayed death in Plasmodium falciparum

Abstract: The malaria parasite Plasmodium falciparum relies on efficient protein translation. An essential component of translation is the tryptophanyl-tRNA synthetase (TrpRS) that charges tRNAtrp. Here we characterise two isoforms of TrpRS in Plasmodium; one eukaryotic type localises to the cytosol and a bacterial type localises to the remnant plastid (apicoplast). We show that the apicoplast TrpRS aminoacylates bacterial tRNAtrp while the cytosolic TrpRS charges eukaryotic tRNAtrp. An inhibitor of bacterial TrpRSs, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 55 publications
1
33
0
Order By: Relevance
“…Although IPP is now used increasingly to discriminate whether or not a drug has a target in the apicoplast, we performed IPP supplementation trials on parasites exposed to two definite nonapicoplast drugs (chloroquine and atovaquone) and two validated apicoplast drugs (azithromycin and fosmidomycin) to establish a comprehensive set of assays focused on apicoplast target validation (Table 1 and Fig. 1) (30,(37)(38)(39)(40)(41)(42). Chloroquine targets the food vacuole in which the parasite digests ingested hemoglobin (43,44), and atovaquone targets the cytochrome bc 1 complex in the mitochondrion (45,46).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although IPP is now used increasingly to discriminate whether or not a drug has a target in the apicoplast, we performed IPP supplementation trials on parasites exposed to two definite nonapicoplast drugs (chloroquine and atovaquone) and two validated apicoplast drugs (azithromycin and fosmidomycin) to establish a comprehensive set of assays focused on apicoplast target validation (Table 1 and Fig. 1) (30,(37)(38)(39)(40)(41)(42). Chloroquine targets the food vacuole in which the parasite digests ingested hemoglobin (43,44), and atovaquone targets the cytochrome bc 1 complex in the mitochondrion (45,46).…”
Section: Resultsmentioning
confidence: 99%
“…These include isoprenoid precursor biosynthesis, fatty acid biosynthesis, Fe-S cluster assembly, and heme biosynthesis (13)(14)(15)(16). The apicoplast is thus indispensable, and either genetic or pharmaceutical perturbation of its activities kills parasites, making the apicoplast a valid drug target (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…36,45,46 Other indole compound, indolmycin, inhibit the protein translation in P. falciparum apicoplast by inhibiting the tryptophanyl-tRNA synthetase leading to a delayed death of the parasite. 47,48 Since PfeIK1parasites were susceptible to indole derivatives, we also investigated if PfeIK1 knockout would interfere with susceptibility of parasite against classical antimalarials. Zhang et al 49 have reported that parasite treatment with artemisinin resulted in an increase in eIF2 phosphorylation by PK4, and inhibition of this kinase can avoid that parasites enter in latency.…”
Section: Discussionmentioning
confidence: 99%
“…In this parasite, an essential pathway proposed as a drug target is the protein synthesis machinery (Goodman et al, 2016). P. falciparum employs eukaryotic protein synthesis machinery for translation of nuclear-encoded mRNAs, however, an endosymbiotic organelle, the apicoplast, carries out translation using machinery that resembles prokaryotes (Chaubey et al, 2005;Fichera and Roos, 1997;Roy et al, 1999) and is the target of several anti-malarial drugs (Goodman et al, 2016;Pasaje et al, 2016). Interestingly, the cytosolic translation machinery of P. falciparum also exhibits differences from that of the human host (Jackson et al, 2011;Wong et al, 2014) and hence, has also been proposed to be a drug target (Sheridan et al, 2018;Wong et al, 2017).…”
Section: Introductionmentioning
confidence: 99%